One mean ant with fly and flea [book with audioplayer] - Yorinks, Arthur (Library Ideas, LLC, 2022)
Ant and Fly are back! And this time they're joined by Flea, newly escaped from the flea circus. Our mean Ant, the meanest ant there ever was, doesn't think much of the tiny, annoying Flea, until Flea's wits get them out of one sticky situation and . . . straight into another. Ant's famous temper can't save them now. The bugs are truly stuck with one another! Author Arthur Yorinks and illustrator Sergio Ruzzier return for the second story in a planned trilogy that introduces a new insect in each book. Picking up where the last tale left off, the text crackles with snappy banter and silly wordplay, while expressive illustrations capture all the entomological action. At heart an ode to the small but mighty, this zany sequel will deliver big laughs for the read-aloud crowd.